Effects of intercropping with post-grafting generation of Impatiens balsamina on photosynthesis of grape seedlings under cadmium stress. Issue 4 (February 2019) - Huan, Yunmin; Wang, Ting; Xia, Dan; Lin, Lijin; Liao, Ming'an
Abstract: To study the effects of intercropping with post-grafting generation of Impatiens balsamina on photosynthesis of grape seedlings, a plurality of photosynthesis indicators of the grape were measured by a pot experiment. The results showed that intercropping with ungrafted and post-grafting generation of I. balsamina all reduced the photosynthesis parameters of grape to some extent. After four intercropping treatments, the net photosynthetic rate (Pn), stomatal conductance (Gs), CO2 concentration of intercellular (Ci), transpiration rate (Tr) and value of pressure deficit leaf (Vpdl) were all lower than that of grape monoculture. Therefore, intercropping with post-grafting generation of I. balsamina could not improve but reduce the photosynthesis of grape seedling.